A Bombesin-Shepherdin Radioconjugate Designed for Combined Extra- and Intracellular Targeting - Christiane A. Fischer; Sandra Vomstein; Thomas L. Mindt (MDPI AG, 2014)
Radiolabeled peptides which target tumor-specific membrane structures of cancer cells represent a promising class of targeted radiopharmaceuticals for the diagnosis and therapy of cancer. A potential drawback of a number of reported radiopeptides is the rapid washout of a substantial fraction of the initially delivered radioactivity from cancer cells and tumors. This renders the initial targeting effort in part futile and results in a lower imaging quality and efficacy of the radiotracer than achievable. We are investigating the combination of internalizing radiopeptides with molecular entities specific for an intracellular target. By enabling intracellular interactions of the radioconjugate, we aim at reducing/decelerating the externalization of radioactivity from cancer cells. Using the "click-to-chelate" approach, the 99mTc-tricarbonyl core as a reporter probe for single-photon emission computed tomography (SPECT) was combined with the binding sequence of bombesin for extracellular targeting of the gastrin-releasing peptide receptor (GRP-r) and peptidic inhibitors of the cytosolic heat shock 90 protein (Hsp90) for intracellular targeting. Receptor-specific uptake of the multifunctional radioconjugate could be confirmed, however, the cellular washout of radioactivity was not improved. We assume that either endosomal trapping or lysosomal degradation of the radioconjugate is accountable for these observations.